DO MACROECONOMICS AND COMMODITIES PREDICT STOCK MARKET? : An Evidence From GARCH Model - Laksono, Gunadi; Eka Puspita, Mutiara (Fakultas Ekonomi, Bisnis dan Humaniora, 2024)
The stock market is a leading indicator and barometer of a nation’s economics and is influenced by a wide of factors, including macroeconomic conditions and global commodity prices. One of the consequential effects of the stock market is foreign exchange. International commodity prices, such as tin, may have an impact on the stock market too. Foreign exchange and the stock market are two significant components of the financial system, and the price of commodities has been a concern for industrialists, economists, and researchers in recent years. This research examines the effect of foreign exchange and commodities on the stock market, uses daily data from the beginning of January 2020 to the end of December 2023, and applies the Generalized Auto Regression Conditional Heterokedasticity (GARCH) method. The findings show that foreign exchange has a negative significant effect on the stock market, while commodities have a positive and significant effect on the stock